Assessement of the influenza burden in nursing homes during two influenza seasons. (13th November 2019) - Qalla-Widmer, L; Petignat, C
Abstract: : Influenza is a significant cause of morbidity and mortality in elderly. They are at high risk of complications after influenza virus infection. Data on the epidemiology of influenza within nursing homes (NH) are limited. The purpose of this prospective study was to better describe the burden of influenza among residents of NH of canton of Vaud, Switzerland, with influenza-like illness during 2016-2017 and 2017-2018 influenza seasons. First, we determined the proportion of influenza-like illness due to influenza in NH residents. We specifically assessed the impact of a positive influenza PCR on clinical features, morbidity and mortality, 30 and 90 days after diagnosis, as compared to a negative influenza PCR. Moreover, influenza vaccination rates of the residents and the healthcare workers within each nursing home were assessed at the end of each influenza season. A PCR test was performed on 509 residents from 61 NH. 227 influenza virus infections were diagnosed; 181 influenza A and 46 influenza B. Compared to residents without influenza virus infection (IVI), residents with IVI were more often feverish with a high fever (69.1% and 88.5% respectively, p < 0.0001) are significantly more frequently hospitalized within 30 days after diagnosis (17.6% vs 7.1%, p = 0.0003). Any cause mortality at 30 days was similar in both groups (12.8% vs 10.6%, p = 0.48). Only 18.1% of IVI residents were treated with an antiviral and 60.4% of them received antibiotics. Influenza vaccination rates of the healthcare workers and residents were respectively 50% and 82%. During influenza season, the feverish residents should be suspected to have influenza virus infection. Residents should be diagnosed (PCR) and treated with an antiviral where appropriate to limit the risk of hospitalization. Healthcare workers should be encouraged to be vaccinated against influenza in order to acquire a better herd immunity within the NH which will limit the spread of influenza. Key messages: Influenza virus in nursing homes is not treated enough. Influenza virus infection in nursing homes causes a high number of hospitalizations.